Regional Variations in Axial Spondyloarthritis in Latin America: A 2019-2024 Analysis of the ESPALDA Registry (2025)
To compare demographic, clinical, functional and therapeutic characteristics of patients with axial spondyloarthritis (axSpA) across three Latin American regions using data from the Registro de Espondiloartritis Axial de America (ESPALDA registry) in the period between January 2019 and December 2024. This cross-sectional study included 418 patients who met the Assessment of SpondyloArthritis International Society (ASAS) criteria for axSpA. Participants were recruited from three Latin American regions: Northern (Mexico), Andean (Colombia, Ecuador, Peru, Venezuela), and Southern (Argentina, Chile, Paraguay, Uruguay). Data were collected on demographic characteristics, HLA-B27 positivity, extra-articular manifestations, disease activity, radiographic damage, and treatment patterns.